Implementasi Media Permainan Ular Tangga Modifikasi untuk Meningkatkan Konsentrasi dan Pemahaman Siswa pada Materi Operasi Hitung Bilangan Berpangkat - Muhibbul Iqrom; Robiatul Adawiyah; Dewi Putri Yanti; Leny Nur Kholisah Mustaman; Moh. Syadidul Itqan; Puji Rahayu (SANISKALA : Jurnal Pengabdian Masyarakat, 2026)
This Community Partnership Program (PKM) activity aims to develop and implement the Modified Snakes and Ladders learning media as an effort to improve students' concentration and understanding of the material on arithmetic operations with powers of numbers, especially after recess when learning focus tends to decrease. This game media is designed by adding question cards containing exercises on the application of exponent properties in each specific box. The implementation of the activity includes the preparation stage, socialization, teacher mentoring, implementation of the game with grade VIII students of Nurul Jadid Paiton Probolinggo Middle School, and evaluation of the media's effectiveness. The results of the activity show that the use of the Modified Snakes and Ladders can increase student activity, motivation, and concentration in learning. Based on the questionnaire, 87% of students stated that learning became more enjoyable, 82% found it easier to concentrate after recess, and teachers considered this media suitable for use in learning. In addition, there was an increase in students' average scores of 18–22% after using the media. Thus, the Modified Snakes and Ladders media is proven to be effective as an innovative learning strategy based on Game-Based Learning that can strengthen understanding of exponent concepts and encourage an interactive, collaborative, and enjoyable learning atmosphere